Active and Transformational Engagement with Writing Feedback: Using Reflection as a Tool to Access Literary Disciplinary Knowledge - Håkansson, Sara; Turner, Ellen; Lecaros, Cecilia Wadsö (Nordic Journal of English Studies, 2021)
This article explores ways of encouraging student engagement with feedback on literature essays. In addition to standard practice of student-centred peer review coupled with feedback from teachers, we have developed a scaffolded pair of reflection tasks on an introductory-level English literature course. With a focus on our two-step model for student self-reflection, this article highlights some challenges in encouraging active and transformational student engagement with feedback they receive from their peers as well as from their teacher. Based on a study of 243 student reflections submitted during an introductory-level English literature module at a Swedish university from 2018 to 2019, we propose that scaffolding students’ reflection practices is beneficent not only for their individual development as writers of academic texts, but also for their ability to address and engage with comments from peers and teachers.